Prevalence of Microalbuminuria in Patients of Essential Hypertension and its Correlation with Left Ventricular Hypertrophy and Carotid Artery Intima‑media Thickness - Pathak, S. R.; Bhattarai, N.; Baskota, D.; Koju, R. P.; Humagain, S. (Kathmandu University Medical Journal, 2022)
Background Urinary albumin excretion has been associated to cardiovascular events and increased mortality in hypertensive patients. There is limited information among Nepalese patients about the implications of microalbuminuria (MA) in the setting of hypertension and potential cardiovascular morbidity.Objective To investigate the prevalence of microalbuminuria in patients with essential hypertension and its connection with left ventricular hypertrophy (LVH) and carotid artery intima-media thickness (cIMT).Method The study involved 80 hypertension individuals in total. All patients in the study had basic biochemical tests, routine urine evaluations, echocardiography, and carotid artery intima-media thickness measurements performed, and the data were analyzed.Result The prevalence of microalbuminuria was present in 37.5% cases of essential hypertension. The mean left ventricular mass index (LVMI) was significantly higher in patients with increased microalbuminuria as compared to patient with normal microalbuminuria. In addition, a significant positive correlation between microalbuminuria and left ventricular hypertrophy was also observed. Furthermore, mean carotid artery intima-media thickness was found to be higher in patients with microalbuminuria (p < 0.001), with 76.7% of the patients with microalbuminuria having elevated mean carotid artery intima-media thickness. The carotid artery intima-media thickness had a positive correlation with both microalbuminuria and left ventricular hypertrophy.Conclusion Microalbuminuria assessment in hypertensive patients is an important test for the evaluation of target organ damage. This study shows that microalbuminuria is common in hypertension patients, particularly those with left ventricular hypertrophy. Microalbuminuria was found to be associated with left ventricular hypertrophy and carotid artery intima-media thickness.